Developing Concept of Walking Aid for Stroke Survivors - Mahrus Khoirul Umami; Hakam Muzakki; Imam Basori; Muhammad Sumardhan; Andre Prasetyo Darmawan (Engineering Proceedings, 2025)
This study aims to develop a walking aid model, for stroke survivors. The design of this assistive device focuses on increasing stability and support for correct body posture, as well as ease of use. The concept’s development processes include identifying user needs, generating device concepts, and selecting a final concept. The user-centered design was applied in the concept development, especially in its conformity with the users’ anthropometry and mechanical capacity, as well as the product safety principles. Mechanical load analysis of the design was also carried out to meet the functionality of the device and used as a foundation for prototype development. The developed device is expected to contribute to improving the quality of life of stroke survivors, since they regain their ability to complete many of their daily activities by themselves.